Symbiotic Effectivity of Dual and Tripartite Associations on Soybean (Glycine max L. Merr.) Cultivars Inoculated With Bradyrhizobium japonicum and AM Fungi - Takács, Tünde; Cseresnyés, Imre; Kovács, Ramóna; Parádi, István; Kelemen, Bettina; Szili-Kovács, Tibor; Füzy, Anna (Frontiers in Plant Science, 2018)
Soybean (Glycine max L. Merr.) is regarded worldwide as indisputably one of the most important crops for human food and animal feed. The presence of symbiotic bacteria and fungi is essential for soybean breeding, especially in low-input agricultural systems. Research on the cooperation between different microbial symbionts is a key to understanding how the health and productivity of the plant is supported. The symbiotic effectivity of dual and tripartite symbiotic agents was investigated in two pot experiments on different soybean cultivars with special regard to compatibility. In the Selection experiment, two out of sixteen soybean cultivars (Aliz, Emese) were chosen on the basis of their drought tolerance and used in all the other investigations. In the Compatibility experiment, the compatible coupling of symbiotic partners was selected based on the efficiency of single and co-inoculation with two Bradyrhizobium japonicum strains and two commercial arbuscular mycorrhizal fungal (AMF) products. Significant differences were found in the infectivity and effectivity of the microsymbionts. The rhizobial and AMF inoculation generally improved plant production, photosynthetic efficiency and root activity, but this effect depended on the type of symbiotic assotiation. Despite the low infectivity of AMF, inocula containing fungi were more beneficial than those containing only rhizobia. In the Drought Stress (DS) experiment, co-inoculated and control plants were grown in chernozem soil originating from organic farms.. Emese was more resistant to drought stress than Aliz and produced a bigger root system. Under DS, the growth parameters of both microbially inoculated cultivars were better than that of control, proving that even drought tolerant genotypes can strengthen their endurance due to inoculation with AMF and nitrogen fixing bacteria. Root electrical capacitance (CR) showed a highly significant linear correlation with root and shoot dry mass and leaf area. The same root biomass was associated with higher CR in inoculated hosts. As CR method detects the absorptive surface increasing due to inoculation, it may be used to check the efficiency of the microbial treatment.